2013
DOI: 10.1136/bmjopen-2013-003126
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of strategies to reduce meticillin-resistantStaphylococcus aureusrates in surgical patients: a controlled multicentre intervention trial

Abstract: ObjectiveTo compare the effect of two strategies (enhanced hand hygiene vs meticillin-resistant Staphylococcus aureus (MRSA) screening and decolonisation) alone and in combination on MRSA rates in surgical wards.DesignProspective, controlled, interventional cohort study, with 6-month baseline, 12-month intervention and 6-month washout phases.Setting33 surgical wards of 10 hospitals in nine countries in Europe and Israel.ParticipantsAll patients admitted to the enrolled wards for more than 24 h.InterventionsThe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
59
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 35 publications
0
59
0
Order By: Relevance
“…For patients undergoing clean surgery, there was a significant reduction in MRSA clinical infection for the AST and decolonization (15% per month) arm and for the combined AST and decolonization plus enhanced hand hygiene arm (18% per month). After multivariable analysis, the only significant reduction in clinical MRSA nosocomial infection was for patients undergoing clean surgery in the AST and decolonization (17% per month) arm (15). The results are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 65%
See 3 more Smart Citations
“…For patients undergoing clean surgery, there was a significant reduction in MRSA clinical infection for the AST and decolonization (15% per month) arm and for the combined AST and decolonization plus enhanced hand hygiene arm (18% per month). After multivariable analysis, the only significant reduction in clinical MRSA nosocomial infection was for patients undergoing clean surgery in the AST and decolonization (17% per month) arm (15). The results are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 65%
“…A large multicenter, multinational trial that studied approaches to reduce MRSA in surgical patients was reported by Lee and colleagues (15). The study included 10 hospitals in 9 countries using 33 surgical wards with a total of 126,750 patients and was designed as a prospective trial with a 6-month baseline, a 12-month intervention, and 6-month washout study periods.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In contradistinction, on the basis of the strength of the literature, one could argue that legislative mandates should be expanded from ICU to facility-wide surveillance (9,13). This position is further supported by a recent multicenter study coauthored by Stephan Harbarth (the JAMA Swiss study's lead author) that found screening coupled with contact precautions and decolonization to be effective in preventing MRSA infections in surgical wards (30).…”
mentioning
confidence: 62%